Carpal tunnel syndrome in vibration disease. - Koskimies, K (1990)
The presence of carpal tunnel syndrome (CTS) in 125 forestry workers with exposure to vibration was examined clinically by electromyography and by determining vibration detection thresholds. Numbness of the hands was present in 43%, history of diminished hand muscle force in 15%, and Raynaud's phenomenon in 27%. The muscle weakness correlated significantly with motor nerve conduction velocity in the median nerve in both hands. In 25 forestry workers CTS was diagnosed. The condition was bilateral in 48%; otherwise it was more common on the right side. Fifteen patients were referred for surgery but because of spontaneous recovery or refusal by the patients only five underwent surgery; of these four improved. The motor conduction velocity of the ulnar nerve was decreased among patients with CTS supporting the idea that entrapment neuropathies in the hands may be due to tissue swelling caused by vibration at work. Total exposure time to vibration correlated with the decrease in motor conduction velocity in the ulnar nerve.